(3GdLhGgQ GdecddI def QGe GdWQb GdecedI aj GdbQGAGJ GdYTQs - (3GdYhaj, eMeO Hf CMeO, J (B1050 (3g`s ((3eMeO Hf Ndjds)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj gOGfG dJdGhI cJGHg hHYO ajbhd eMeO Hf GMeO GdYhaj GNJUQJ cJGHj GdeSei HMQ GdeYGfj hcfR GdSHY GdeKGfj hSejJg GdLhGgQ GdecddI HGH CSeGA GdbQGA hGdQhGjI fGaY ef s
(3BNQgG (B:s
(3EPG SLOJ aj BNQ GdYdb Ydi Gdbhd HGfg dBNQ GdShQI cHQJ ddShQI Ke cHQJ ddSLOI hYdi GdBNQ cHQJ ddSLOI abW Ke jHJOF HGdJcHjQ dShQI GdbOQ hGddg CYdes
(3efShNI ef fSNI GdeDda GdeDQNI (B: 1049 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 9s
(3eYLe GdeDdajf (B3 / 89s
(3gOjI GdYGQajf (B2/ 263s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs